2020
DOI: 10.1039/d0sm00001a
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in the science of complex coacervation

Abstract: We review recent progress in the science of polymeric complex coacervation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
479
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 443 publications
(540 citation statements)
references
References 327 publications
16
479
2
Order By: Relevance
“…The assembly is observed as a micrometer-sized liquid droplet under optical microscopes, which is distinct from polyplexes, which are observed as solid precipitates under the optical microscopes if they are large enough to be observed as the cases of those formed with homo-polycations. Such droplets are typically formed from single-stranded oligo DNA or RNA in the presence of salt, whereas the double-stranded alternatives tend to precipitate under the same condition [10][11][12]118]. Notably, it was observed that oligo double-stranded DNA, approximately 20 bp, melted once incorporated in droplets [119].…”
Section: Discussionmentioning
confidence: 99%
“…The assembly is observed as a micrometer-sized liquid droplet under optical microscopes, which is distinct from polyplexes, which are observed as solid precipitates under the optical microscopes if they are large enough to be observed as the cases of those formed with homo-polycations. Such droplets are typically formed from single-stranded oligo DNA or RNA in the presence of salt, whereas the double-stranded alternatives tend to precipitate under the same condition [10][11][12]118]. Notably, it was observed that oligo double-stranded DNA, approximately 20 bp, melted once incorporated in droplets [119].…”
Section: Discussionmentioning
confidence: 99%
“…The final measurement parameter measurements for each droplet are taken as those from the z-plane with the best fit, typically with Adj. R 2…”
Section: Qpm Measures the Refractive Index Of Micron-sized Droplets Imentioning
confidence: 99%
“…Complex coacervation, [49,51,52,56,57,[61][62][63][64][65][66][67][68][69][70][71][72][73] whose characteristics mimic the characteristics of cells, is a simple, purely aqueous strategy for encapsulating proteins. Complex coacervation is a liquid-liquid phase separation phenomenon resulting from the association of two oppositely charged macro-ions (e.g., polymer, protein, surfactant micelles).…”
Section: Complex Coacervation Phase Behavior and Biomimicrymentioning
confidence: 99%